Cores e sombras da visita domiciliar na Estratégia Saúde da Família: perspectivas de profissionais e usuários - MOURA, Márcia Raquel Lima Amaral (2014)
The home visit is a way of training professionals for its insertion and the knowledge of the reality of life for families, as well as the establishment of relationships, in order to meet the different health needs of each individual/community. In this context, the Family Health Team must conduct its activities in the home environment in accordance with the family and their relationships based on respect, ethics, humanization and dignity. In view of this reality it was considered as a starting point: the concepts of Hall regarding the relationship that man makes with the space in the communication process. We start from the assertion that personal attitudes as well as the aspects that relate to the organization and structure of services, affect the work process and home visit as an instrument of care in Primary Health. From this perspective is questioned: What reveal professionals and users of the Family Health Strategy on home visits as a tool for health care? This is an exploratory study, descriptive, with qualitative approach in order to understand about the perspective of professionals and users of the Family Health Strategy, the operational process of home visits as a tool for health care. The research was developed in seven Family Health Teams in peripheral suburbs in the City of São Luís, capital of Maranhão. We totaled 86 participants between 52 Family, 4 Doctors, 7 Nurses, 6 Nursing Technicians and 17 Community Health Agents. To obtain the data, we used the open and unstructured interview with analysis of data from the thematic analysis. The product of this process has resulted in the construction of seven subjects: 1) Identifying Feelings of Satisfaction Related to Home Visit; 2) Work Process in Home Visit; 3) Citizenship Users: silence, privacy, confidentiality and autonomy; 4) Experiencing the home visit as Instrument Care; 5) Recognizing the Responsible for realization of the Home Visit; 6) Demonstrating the home visit as a Strategy for Creating Link between Professional and Community and 7) Establishing Criteria for Priority Realization of Home Visits. The process of research and careful analysis of the data possible to seize the home visit in the Family Health Strategy is permeated by strengths and weaknesses for health care. Revealed the requirement of professional attitudes to adopt to listen, speak and understand the unspoken order to share, pursue or retreat setting proper correlation between space and link with the objective to identify and plan for health care in the context of family and community. However, the Family Health Teams without health workers and doctors, as well as rate stay high turnover and the last represent weaknesses for the operationalization of the home visit with ethical implications that extends to the management of health services.